2018
DOI: 10.1002/bdr2.1219
|View full text |Cite
|
Sign up to set email alerts
|

Large for gestational age and macrosomia in singletons born after frozen/thawed embryo transfer (FET) in assisted reproductive technology (ART)

Abstract: Increase in success rates with frozen embryo transfer (FET) and reduced risk of ovarian hyperstimulation syndrome (OHSS) and multiple pregnancies has lead to a steady rise in FET. Further, FET is associated with lower risk of prematurity and low birth weight in singletons, when compared with fresh transfer. However, there is a growing concern of increased risk of large for gestational (LGA) and/or macrosomic children after FET. Macrosomic/LGA births have a higher risk of cesarean section, fetal hypoxia and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 53 publications
(100 reference statements)
1
37
0
1
Order By: Relevance
“…Luke et al (27) found that in siblings sharing the same mother, children born after FET had a higher risk of LGA than their siblings born after fresh ET (27). Berntsen and Pinborg (28) evaluated the association between FET and LGA and/or macrosomia. Their meta-analysis, consisting of 10 studies on LGA and 6 on macrosomia has revealed that the risk of LGA in FET was increased 1.5-fold and 1.3-fold compared to fresh cycles and NC, respectively.…”
Section: Fet Pregnanciesmentioning
confidence: 99%
“…Luke et al (27) found that in siblings sharing the same mother, children born after FET had a higher risk of LGA than their siblings born after fresh ET (27). Berntsen and Pinborg (28) evaluated the association between FET and LGA and/or macrosomia. Their meta-analysis, consisting of 10 studies on LGA and 6 on macrosomia has revealed that the risk of LGA in FET was increased 1.5-fold and 1.3-fold compared to fresh cycles and NC, respectively.…”
Section: Fet Pregnanciesmentioning
confidence: 99%
“…Even if assisted reproductive technologies (ARTs) are successful in many species, in vitro embryos differ from their in vivo derived counterparts in terms of their cryotolerance, lipid content and developmental competence (reviewed in Rizos et al, 2008). Furthermore, epidemiological human studies have shown altered birthweight profiles in ART compared with spontaneously conceived singletons (Berntsen & Pinborg, 2018;Hunter, 2017). While conception with cryopreserved embryos resulted in a higher risk of large-for-gestational-age babies, conception with fresh embryos had a higher risk for small-for-gestational-age babies (Berntsen & Pinborg, 2018;Hunter, 2017).…”
Section: Appli C Ati On Of Ali Culture S For Reproduc Tive B I Ologmentioning
confidence: 99%
“…Furthermore, epidemiological human studies have shown altered birthweight profiles in ART compared with spontaneously conceived singletons (Berntsen & Pinborg, 2018;Hunter, 2017). While conception with cryopreserved embryos resulted in a higher risk of large-for-gestational-age babies, conception with fresh embryos had a higher risk for small-for-gestational-age babies (Berntsen & Pinborg, 2018;Hunter, 2017). Further animal studies in offspring conceived via ART found altered gene expression profiles related to glucose metabolism.…”
Section: Appli C Ati On Of Ali Culture S For Reproduc Tive B I Ologmentioning
confidence: 99%
“…Результаты метаанализа показали существенную разницу в частоте LGA после FET и переноса свежих эмбрионов (ОШ 1,50; 95% ДИ 1,44-1,57; p<0,001), а также после FET и NC (ОШ 1,31; 95% ДИ 1,20-1,43; р<0,001). Установлены и различия в частоте развития макросомии плода после FET и переноса свежих эмбрионов (ОШ 1,71; 95% ДИ 1,59-1,83; p<0,001), а также после FET и NC (ОШ 1,42; 95% ДИ 1,17-1,71; p<0,001) соответственно [36].…”
Section: перинатальные исходыunclassified